Examination of Innovative Wastewater Treatment Method for Chemical Treatment of Municipal Wastewater - Truzsi, Alexandra; Bodnár, Ildikó; Fülöp, Zoltán (International Journal of Engineering and Management Sciences, 2016)
The VízTEC Ltd. and Debrecen Waterworks Co.’s management mutually expressed their intention, that to designate a period of research examining the Debrecen Waste Water Treatment Plant’s (WWTP) intensification. During this period, the newly developed product, VIRON Plus 40 coagulating agent will be tested provided by the VízTEC Ltd. The aim of using the VIRON Plus 40 coagulating agent is the examination of intensification opportunities of Debrecen WWTP. The functions of the new generation of coagulants go beyond inorganic phosphorus precipitation and are growing. A modern WWTP is not only clean the water but also produces energy and usable sludge product. The appropriate energy balance, cost efficiency and carbon dioxide emissions reduction get increasing emphasis in WWTP’ operations.